Assessment of microbiological safety and physicochemical changes of grey oyster mushroom (Pleurotus sajor-caju) during storage at 4 °C and 25 °C - Suhaili M.,; Nor-Khaizura M.A.R.,; Nur Hanani Z.A.,; M.R. Ismail-Fitry,; N.I.P. Samsudin,; N.N. Jambari, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study aimed to evaluate the microbiological and physicochemical properties of grey oyster mushroom during storage (day 0, 3, 6, 9, 12) at 4 °C and 25 °C. The microbial quality and safety analyses were aerobic plate count (APC), yeast and mould count, Escherichia coli count, Bacillus cereus count, and Listeria monocytogenes count, while the physicochemical analyses were pH, water activity, colour, and firmness. Grey oyster mushroom stored at 4 °C showed increasing trend in all microbial counts. A similar trend was observed at 25 °C, but with higher microbial counts except for L. monocytogenes which had a slight reduction from 1.82 ± 1.16 at day 0 to 0.24 ± 0.34 log CFU/g at day 6. The pH of grey oyster mushroom was quite stable when stored at 4 °C (6.42 ± 0.03 at day 0 to 6.46 ± 0.21 at day 12). A decrease in pH was observed when the mushroom was stored at 25 °C (6.42 ± 0.03 at day 0 to 5.38 ± 0.93 at day 6). The Browning Index (BI) increased which indicated by the colour changes on the mushroom cap (front and back) especially at 25 °C. Firmness analysis carried out on mushroom cap and stalk showed a decreasing trend during storage, at which 25 °C displayed prominent loss of firmness in cap and stalk as compared to 4 °C. In conclusion, slower deterioration was observed in grey oyster mushroom stored at 4 °C as compared to 25 °C. This is based on lower microbial counts, and minimal changes in pH, BI, and firmness of grey oyster mushroom.